Medical microbiology : made easy - Ahluwalia, Jyotica (Jaypee Brothers Medical Publishers Pvt Ltd, 2018)
Medical microbiology is a branch of medical science concerned with the prevention, diagnosis and treatment of infectious diseases. This book is a comprehensive guide to microbiology for undergraduate and postgraduate students. Beginning with an overview of bacteriology, the text goes on to explain biofilms (one or more types of microorganism that can grow on many different surfaces including bacteria, fungi and protists), and hospital waste management. The following sections cover advances in diagnostic techniques, then explore the subspecialties of microbiology - immunology, pathogenic bacteriology, parasitology, virology, and mycology. Each chapter is presented in a text and bullet point format to emphasise the key points. Self-assessment questions conclude each topic to assist revision. Key points. Comprehensive guide to microbiology for students. In depth discussion on subspecialties such as immunology, parasitology and virology. Includes self-assessment questions to assist revision. Further enhanced by clinical images and figures.